Computer Generation of Low Light-Level Images - N. Hassan, Raaid; S. Ali, Huda (Iraqi Journal of Science, 2023)
As result of exposure in low light-level are images with only a small number ofphotons. Only the pixels in which arrive the photopulse have an intensity valuedifferent from zero. This paper presents an easy and fast procedure for simulatinglow light-level images by taking a standard well illuminated image as a reference.The images so obtained are composed by a few illuminated pixels on a darkbackground. When the number of illuminated pixels is less than 0.01% of the totalpixels number it is difficult to identify the original object.